Design and fabrication of double automatic can crusher / Adib Farhan Badrol Isa - Badrol Isa, Adib Farhan (2023)
The invention of a can crusher machine in this project is to reduce the wasted storage space occupied by the many amount of use aluminium can at the commercial establishment like in the groceries, restaurant and bar. So basically, can crusher machine be operated in manual effort and time in the cane crushing process. Shrinking the initial volume of empty used-aluminium cans down to 50% in more effective, faster and effortless way, as well as to develop a low-cost device that is suitable for the small- industry usage are mainly the objectives for the Double Automatic Can Crusher, where an automated process is executed in Double Automatic Can Crusher due to the automation in the modern world is nominal to be used. The Double Automatic Can Crusher is run by Motor Ac and Batteries. Overall, the system can be controlled manually through the push start and stop button as well as using the Human Machine Interface (HMI), for displaying the total of cans being crushed per day. The average result of empty can could shrink from 31% to 60 % of the original value, by using motor Ac and gear for this system.